2021
DOI: 10.3389/fendo.2021.787854
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Effect of Epilepsy and Antiseizure Medications on PCOS Through HPO Axis

Abstract: Epilepsy is a common chronic neurological disease that manifests as recurrent seizures. The incidence and prevalence of epilepsy in women are slightly lower than those in men. Polycystic ovary syndrome (PCOS), a reproductive endocrine system disease, is a complication that women with epilepsy are susceptible to, and its total prevalence is 8%–13% in the female population and sometimes as high as 26% in female epilepsy patients. The rate of PCOS increased markedly in female patients who chose valproate (VPA), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 147 publications
(229 reference statements)
2
8
0
Order By: Relevance
“…Our findings show that LTG has a better safety profile compared to other anticonvulsant mood stabilizers. This is consistent with the findings of Li et al ( 16 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings show that LTG has a better safety profile compared to other anticonvulsant mood stabilizers. This is consistent with the findings of Li et al ( 16 ).…”
Section: Discussionsupporting
confidence: 94%
“…In recent years, studies by Zhang et al ( 15 ) have shown that the use of VPA is associated with an increased incidence of PCOS. Some studies have also reported adverse reactions to anticonvulsant mood stabilizers such as CBZ and LTG, such as menstrual disorders, obesity, and abnormal reproductive hormones ( 12 , 16 ). However, the current studies have all focused on the phenomenon of PCOS triggered by a particular drug, and few studies have compared the probability of PCOS triggered by different drugs to give a reference on the clinical use of anticonvulsant mood stabilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Hypothalamic control of reproduction is coordinated by the pulsatile release of gonadotropin-releasing hormone (GnRH) from the arcuate nucleus of the hypothalamus through the pituitary portal system, which acts on the pituitary gland and regulates the secretion of luteinizing hormone (LH) and follicle-stimulating hormone (FSH). The latter acts on the ovaries to stimulate follicular growth and promote the release of sex steroids, such as testosterone (T), estradiol (E2), and progesterone (P4) [ 5 , 56 ]. On the one hand, such hormonal changes might be hypothalamic-pituitary abnormalities or negative feedback abnormalities; on the other hand, PCOS patients with DOR might have follicle stagnation in the preantral follicular phase, with antral follicles reduced accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated that women with epilepsy (WWE) have a higher propensity for developing metabolic or hormonal irregularities compared to their healthy counterparts of similar age, 2 eg, the prevalence of polycystic ovary syndrome (PCOs) in women with endocrine disorders (WWE) is estimated to be around 10-25%, whereas in the general population, it varies between 8% and 13% due to variations in diagnostic criteria and ethnic disparities. 3 In this review, we delve into the endocrine aberrations encompassing thyroid hormones, bone metabolism, and sex hormones, elucidating their enduring repercussions on women, their fetuses during gestation, and subsequent stages of life (Figure S1). This comprehensive analysis scrutinizes the available evidence pertaining to the matter of endocrine dysfunctions in WWE with endocrine disorders, while also highlighting the necessary actions to be undertaken in the forthcoming period.…”
Section: Introductionmentioning
confidence: 99%